2007
DOI: 10.1007/s10463-007-0115-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric inference for sequential k-out-of-n systems

Abstract: Sequential k-out-of-n systems, Nonparametric estimation, Nonparametric hypothesis testing, Nelson–Aalen estimator, Martingale methods,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…General properties and other practical applications of SOS models can be found in Refs. [1,4,[10][11][12]16,19] and in the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…General properties and other practical applications of SOS models can be found in Refs. [1,4,[10][11][12]16,19] and in the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…For further details on sequential order statistics, in particular concerning statistical inference, we refer to, e.g., Kamps (2006), Cramer and Kamps (1996, 2001a,b, 2003, Balakrishnan, Beutner and Kamps (2008), Beutner (2008Beutner ( , 2010, Kamps (2009), Burkschat (2009), Burkschat andLenz (2009), Bedbur (2010), Bedbur, Beutner and Kamps (2012), Burkschat, Kamps and Kateri (2010), and Balakrishnan, Kamps and Kateri (2012).…”
Section: Statistical Model and Preliminariesmentioning
confidence: 99%
“…Nonparametric estimation of the cumulative hazard rate function, the reliability function and the quantile function of progressively Type II censored order statistics as well as homogeneity tests for two distribution functions in a sampling situation different from that one considered in Alvarez-Andrade and Bordes (2004), Alvarez-Andrade et al (2007), and Bordes (2004) can be found in Beutner (2007a).…”
Section: Nonparametricsmentioning
confidence: 99%